RESEARCH ON VARIABLE INERTIA CHARACTERISTICS OF RECIPROCATING CRANKSHAFT SYSTEM TAKEN CONNECTING ROD RATIO INTO CONSIDERATION - HAN JianXin; ZHANG QiChang; WANG Wei; JIN Gang; QI HouJun (Jixie qiangdu)
Variation of connecting rod ratio in reciprocating crankshaft system can affect the value of system equivalent moment of inertia. However,current traditional variable inertia formula does not consider this important factor,which induces certain errors during torsional vibration analysis. This paper aims to investigate the effects of connecting rod ratio on equivalent moment of inertia and torsional vibration. First,a modified variable inertia formula concerning connecting rod ratio is deduced and its accuracy is compared with traditional one. Then,torsional dynamic equation is established and the method of multiple scales is used to derive the average equation under primary resonance condition. The effects of connecting rod ratio on stable dynamics of the system are investigated. Moreover,traditional and modified variable inertia formulas are compared with exact variable inertia through a detailed single-cylinder crankshaft system. And the shortage of traditional one is pointed out. Finally,numerical results on system vibration characteristic based on different variable inertia formulas are shown to verify the importance of connecting rod ratio on system performances.